eCM 2011
DOI: 10.22203/ecm.v021a20
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the effects of glucosamine sulphate and chondroitin sulphate on surgically treated and untreated focal cartilage damage

Abstract: The effects of Glucosamine Sulphate (GS) and Chondroitin Sulphate (CS) on the healing of damaged and repaired articular cartilage were investigated. This study was conducted using 18 New Zealand white rabbits as experimental models. Focal cartilage defects, surgically created in the medial femoral condyle, were either treated by means of autologous chondrocyte implantation (ACI) or left untreated as controls. Rabbits were then divided into groups which received either GS+/-CS or no pharmacotherapy. Three rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
3
22
0
1
Order By: Relevance
“…Similar conclusions were reached by authors studying the fixation of similar biomaterials in osteochondral defects in rats and rabbits when compared to control groups without implantation (4,27). In another study of osteochondral defects in rabbits, in groups where defects were left to heal spontaneously, the histopathological and macroscopic assessment of the formed tissue was also unsatisfactory, despite additional oral supplementation with glucosamine sulphate and chondroitin preparations (50). Gradual changes in BAP concentrations observed in the conducted study are consistent with the results reported by Kim et al who studied the behaviour of osteoblasts on porous bases of PLGA copolymer modified with nanohydroxyapatite.…”
Section: In Vivosupporting
confidence: 70%
“…Similar conclusions were reached by authors studying the fixation of similar biomaterials in osteochondral defects in rats and rabbits when compared to control groups without implantation (4,27). In another study of osteochondral defects in rabbits, in groups where defects were left to heal spontaneously, the histopathological and macroscopic assessment of the formed tissue was also unsatisfactory, despite additional oral supplementation with glucosamine sulphate and chondroitin preparations (50). Gradual changes in BAP concentrations observed in the conducted study are consistent with the results reported by Kim et al who studied the behaviour of osteoblasts on porous bases of PLGA copolymer modified with nanohydroxyapatite.…”
Section: In Vivosupporting
confidence: 70%
“…Bioactive factors secreted by MSCs have been shown to inhibit tissue scarring; suppress apoptosis, inflammatory and fibrotic; stimulate angiogenesis where MSCs secrete a growth factor, VEGF (Vascular Endothelium Growth Factor), which stimulates vascularization; and enhance mitosis of tissue-intrinsic stem or progenitor cells. Other studies have shown that MSCs attach to the defect sites while others have shown that in the transplanted site MSCs regress dramatically to a point that they are no longer viable [26,27]. Regardless of the mechanisms involved, the present study clearly demonstrated a correlation between the use of MSCs with superior tissue repair, which will require further investigations if we wish to elicit the mechanisms involved.…”
Section: Discussionsupporting
confidence: 48%
“…In the course of long-term research and observations of patients undergoing reparative treatment conducted by Steadman, among others, the clinical effectiveness of this approach has been generally assessed as satisfactory (8). Analyses of the makeup of the reconstructed tissue revealed that it primarily consists of fibrocartilaginous tissue.…”
Section: Reparative Methodsmentioning
confidence: 99%
“…They revealed that glucosamine sulphate is an efficient analgesic, whose pain-relieving effects last far longer than those of non-steroidal drugs. Furthermore, it helps to inhibit the development of degenerative disease, as measured radiologically with regard to its effect of slowing-down the narrowing of the articular space in human knee joints (8,18).…”
Section: Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation